2008
DOI: 10.1186/1749-8104-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient axonal glycoprotein-1 (TAG-1) and laminin-α1 regulate dynamic growth cone behaviors and initial axon direction in vivo

Abstract: Background: How axon guidance signals regulate growth cone behavior and guidance decisions in the complex in vivo environment of the central nervous system is not well understood. We have taken advantage of the unique features of the zebrafish embryo to visualize dynamic growth cone behaviors and analyze guidance mechanisms of axons emerging from a central brain nucleus in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 53 publications
3
55
0
3
Order By: Relevance
“…Sittaramane et al (Sittaramane et al, 2009) found that Cntn2-deficient specimens have defects in FBMN migration. Interestingly, as well as being expressed in FBMNs, Cntn2 protein is expressed on the MLF and is crucial for MLF fasciculation and pathfinding (Wolman et al, 2008). In preliminary Cntn2-depletion experiments (S.J.W.…”
Section: Research Articlementioning
confidence: 99%
“…Sittaramane et al (Sittaramane et al, 2009) found that Cntn2-deficient specimens have defects in FBMN migration. Interestingly, as well as being expressed in FBMNs, Cntn2 protein is expressed on the MLF and is crucial for MLF fasciculation and pathfinding (Wolman et al, 2008). In preliminary Cntn2-depletion experiments (S.J.W.…”
Section: Research Articlementioning
confidence: 99%
“…TAG-1 is expressed in many neuronal subpopulations as a glycosyl-phosphatidyl-inositol anchored form as well as a released form, and is implicated in neurogenesis, neurite extension, and fasciculation (Furley et Praag, 2008;Wolman et al, 2008;Lieberoth et al, 2009). In the adult, TAG-1 is expressed by neurons and by myelinating glia.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst morpholino knockdown of Sema3D reduces L1 expression, its overexpression increases the surface expression of L1 in MLF axons (Wolman et al, 2007). In addition to L1, other CAMs, such as Tag1 (transiently expressed axonal glycoprotein 1), might be required for proper axon-axon interactions and for the guidance of MLF neurons (Wolman et al, 2008), demonstrating that the formation of even a relatively simple tract is governed by the concerted action of numerous components. Halloran's work is undoubtedly of wider significance, as it promises to inform the investigation of other systems.…”
Section: Regulating Responsiveness At the Receptor Levelmentioning
confidence: 99%